The use of human rights model to address the problem of health care and reproductive rights of women, most importantly victims of obstetric fistula in Africa - Cistac, Doutor Gilles (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2008.